Estimativa da transpiração de cajueiros na Baixada Cuiabana - Matos, Victor Arlindo Taveira de (2017)
The objective of this study was to evaluate the effects of meteorological and plant parameters on the transpiration of cashew plants cultivated in lysimeters in Baixada Cuiabana. The study was carried at the Experimental Farm of the Federal University of Mato Grosso, located in the municipality of Santo Antônio de Leverger, MT (15.8 ° S and 56.1 ° W, 140 m). The local climate, according to the Köppen classification, is the Aw type, tropical humid, with average air temperature around 26°C and average rainfall of 1360 mm annually. In the period from September 2012 to December 2015, using intervals of at least three days, the water consumption of 8 dwarf cashew plants of the EMBRAPA 51 clone was measured. Four plants were grown in the constant level water table lysimeters and the other four in the weighing lysimeters, using one plant by lysimeter, adding water in the weighing lysimeters in the period without rainfall, according to the need. Monthly, each plant had its leaf area determined by a non-destructive method, using measurements of the leaves’ length and width. A model for estimating the transpiration of dwarf cashew plants cultivated in a constant water table lysimeter was developed, based on the relation between the reference evapotranspiration (ETo) – obtained by the Penman-Monteith methods or by the Class A Pan – or evaporation of Class A Pan with the leaf area of plants grown in constant level water table lysimeters. It was also aimed to analyze the effect of soil moisture on the transpiration of cashew plants cultivated in weighing lysimeters and obtain models of transpiration related to the soil moisture, leaf area and local meteorological conditions. The meteorological data were obtained at the agrometeorological station Padre Ricardo Remetter, installed at approximately 10.0 m from the place where the experiment was conducted. It was observed that the plants leaf area and the soil moisture have a direct relation with the effect of the transpiration of the cashew plants. The proposed models were adjusted and presented satisfactory performance. The information obtained will help in the elaboration of management strategies that allow getting an adequate production of cashew for the environmental and market requirements, promoting the incentive of the fruit culture in the region.